2020
DOI: 10.14202/vetworld.2020.1970-1981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of respiratory disease on Kele piglets lung microbiome, assessed through 16S rRNA sequencing

Abstract: Background and Aim: Due to the incomplete development of the immune system in immature piglets, the respiratory tract is susceptible to invasion by numerous pathogens that cause a range of potential respiratory diseases. However, few studies have reported the changes in pig lung microorganisms during respiratory infection. Therefore, we aimed to explore the differences in lung environmental microorganisms between healthy piglets and piglets with respiratory diseases. Materials and Methods: Histopathological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Other genera were identified to be significantly different between TRT and CON calves for the OTU dataset; however, these genera reported herein for the OTU dataset were of low abundance (<5%) and not present in all the lung lavage samples evaluated. While the relative abundance of these taxa is low in the calves evaluated, previous literature has identified several of these taxa, including Lachnospiraceae, Veillonella, Bosea, Sphingobacterium, Porphyromonas, Finegoldia, and Massilia in the microbiome of the respiratory tract of pre-weaned calves (Raabis et al, 2021), feedlot cattle (McMullen et al, 2020a,b), piglets (Zhang et al, 2020), and humans (Hu et al, 2017;Menetrey et al, 2021;Chen et al, 2022).…”
Section: Bacterial Taxa Evaluationmentioning
confidence: 96%
See 1 more Smart Citation
“…Other genera were identified to be significantly different between TRT and CON calves for the OTU dataset; however, these genera reported herein for the OTU dataset were of low abundance (<5%) and not present in all the lung lavage samples evaluated. While the relative abundance of these taxa is low in the calves evaluated, previous literature has identified several of these taxa, including Lachnospiraceae, Veillonella, Bosea, Sphingobacterium, Porphyromonas, Finegoldia, and Massilia in the microbiome of the respiratory tract of pre-weaned calves (Raabis et al, 2021), feedlot cattle (McMullen et al, 2020a,b), piglets (Zhang et al, 2020), and humans (Hu et al, 2017;Menetrey et al, 2021;Chen et al, 2022).…”
Section: Bacterial Taxa Evaluationmentioning
confidence: 96%
“…Of these taxa, Mycoplasma and Myroides have been previously reported to be present in the respiratory tract of pre-weaned calves or feedlot cattle (McDaneld et al, 2019;McMullen et al, 2020a,b;Raabis et al, 2021;Centeno-Martinez et al, 2023). Of the remaining top five genera identified, Elizabethkingia and Stenotrophomonas have been identified in the respiratory tract of piglets and humans (Hu et al, 2017;Zhang et al, 2020;Menetrey et al, 2021;Chen et al, 2022), but current literature has not reported the genus Aeromicrobium as a predominant bacterial taxa present in the respiratory tract. These data suggest that additional research needs to be completed on these bacterial taxa to elucidate the role of these genera in the lungs of cattle.…”
Section: Bacterial Taxa Evaluationmentioning
confidence: 99%
“…A similar 16S rRNA-based study of the lungs of healthy and diseased Duroc × Landrace × Yorkshire crossbreed pigs found a higher relative abundance of Lactococcus , Enterococcus , Staphylococcus, and Lactobacillus in healthy pig lungs and an enhanced richness of Streptococcus , Haemophilus , Pasteurella, and Bordetella genera in diseased lungs, although no diagnostics as to the primary or secondary infections of diseased pigs was reported (Li et al ., 2020). Another 16S rRNA-based study comparing the diversity of bacteria in the alveolar lavage fluid obtained from healthy and diseased lungs of 4-week-old Kele pigs has also been reported (Zhang et al ., 2020). Taken collectively, the results suggest that infection of pig lungs with bacterial pathogens can dramatically alter the microbiome, and that colonization with many divergent beneficial bacteria may have a role in protection of the lungs against pathogenic microorganisms.…”
Section: The Misteachings Framework Applied To Appmentioning
confidence: 99%
“…Особливість циклу розвитку паразитів метастронгілюсів, аскарид і проникнення їх в дихальну систему призводить до прояву респіраторного синдрому на ранніх стадіях росту та розвитку організму. За резуль-татами наукових досліджень прослідковується той факт, що через незавершений розвиток імунної системи, у незрілих поросят, дихальні шляхи сприйнятливі до багаточисленних збудників, які викликають ряд потенційних респіраторних захворювань (Zhang, et al, 2020). На теперішній час у фермерських господарствах, найбільш частими причинами респіраторних захворювань серед свинопоголів'я є збудники P.multocida, M.hyopneumoniae (Zong, et al, 2022).…”
unclassified